A SURVEY ON ALZHEIMER DISEASE IDENTIFICATION USING SEGMENTATION TECHNIQUES (International Journal of Food and Nutritional Sciences, 2022)
Image segmentation is a critical field of research in medical engineering. Segmented brain images are used to assess volume and statistically analyze anatomical and cortical components. Because of advances in Magnetic Resonance Imaging, segmented brain tissues provide an anatomical framework for visualization, with potential uses in neuro-science research and neurosurgery planning (MRI). The technique of separating pixels into discrete sections is known as segmentation. At a higher level, these regions may be recognized as anatomical structures and then aggregated over several slices to offer three-dimensional descriptions of these structures. This article reviews 25 research papers for Alzheimer disease segmentation and explores the potential of computer-assisted methods for Alzheimer disease and staging. This method is useful at segmenting the brain without the need of humans and accurately recognizing differences in the brain's overall volume or size. The goal of this investigation is to detect any minor changes in brain volume.